2019
DOI: 10.1080/13880209.2019.1577461
|View full text |Cite
|
Sign up to set email alerts
|

β-Sitosterol modulates macrophage polarization and attenuates rheumatoid inflammation in mice

Abstract: Context: β-Sitosterol (BS), the primary constituent of plants and vegetables, exhibits multiple biological effects. Objective: This study explores its effect of immune-regulation on macrophages and its potential for rheumatoid arthritis (RA) therapy. Materials and methods: In vitro , bone marrow-derived macrophages (BMDMs) were treated with 5, 25 and 50 μM BS in the M1 or M2 polarization conditions. In vivo , either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 37 publications
(40 reference statements)
1
55
0
2
Order By: Relevance
“…Our ndings decipher that SE fruits extract increased signi cantly two pro-apoptotic key genes Bax and Bad in NP tissues (P < 0.0001). On the other hand, Beta-sitosterol, one of major component of SEs extract (Table2) has a crucial role in inducing apoptosis in NP tissue [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings decipher that SE fruits extract increased signi cantly two pro-apoptotic key genes Bax and Bad in NP tissues (P < 0.0001). On the other hand, Beta-sitosterol, one of major component of SEs extract (Table2) has a crucial role in inducing apoptosis in NP tissue [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that plantain has significant anti-inflammatory activity and can reduce the secretion of TNF- α , IL-10, and IL-6 in the mouse leukemia cells of monocyte macrophage (RAW264.7) inflammatory model [ 71 , 72 ]. It has been proved that compounds dinatin [ 73 ], baicalein [ 35 ], baicalin [ 35 ], sitosterol [ 74 ], stigmasterol [ 44 ], and luteolin [ 45 ] can reduce the level of TNF- α . This suggests that plantain may be a potential treatment for gout and hyperuricemia by inhibiting TNF signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Sitosterol can treat cerebral aneurysms by reducing the expression of chemokines and inflammatory cytokines TNF- α , IL-8, IL-1 β , IL-17, IL-6, and MMP-2/9 [ 43 ]. It can reduce the level of IL-17, TNF- α , IL-1 β , IL-6, and IL-12 in RA mice and promote the production of anti-inflammatory cytokine IL-10 [ 44 , 74 ]. Sitosterol can also treat foot edema caused by MSU crystals in mice [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the Fatty acids are required for innate immune activation and pathogen defense [ 35 ]. Sitosterol is the main constituent of many plants and vegetables and has the ability to modulate the functions of macrophages and anti-inflammation [ 36 , 37 ]. β-carotene also has been shown to suppress the cellular and tissue response to inflammation [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%